Turning around a local automotive company: What type of leadership syles matters? - A. Rahman, Badruddin; Abdullah, Shahmir Sivaraj (2010)
From 2000-2005, Proton’s market share began to erode due to the introduction of AFTA and the inability of the organization to meet the expectations of ever increasing and demanding customers. The open market situation left Proton trailing other global automakers such as Toyota and Honda.Toyota, through its subsidiary company, Daihatsu-Perodua began to command market share from 2005-2008. Toyota which is very much associated with product reliability has been able to translate its forte into Perodua’s product and thus was capable of winning the hearts of customers. Proton on the other hand, is still immersed in a status quo and tends to ignore the change within its business environment. An appropriate Business Turnaround Plan is needed to enable Proton to remain competitive and relevant in the open market and to resolve the issues that has been demanded by their customers all this while. Proton’s second phase mission should focus on these issues and must be clearly defined. A comprehensive plan is essential in order to transform Proton from Malaysian based enterprise to a global player. Proton has to sell it products in the global market with significant volumes in order to survive whilst ensuring its product quality of meets these global standards.The inroad into a high passenger car annual growth rate is very crucial to the survivability of the company. Prudent management is mandatory to turnaround the company. As the erosion of market share became apparent in recent years, a set of new leadership styles must be imposed on the organization and its business operation. When the Business Turnaround Plan (BTP) was first introduced in 2006, there were concerns from a variety of interested parties on the ability of this small Malaysia centered company to compete against the other global car manufacturers. After several grand initiatives were exercised, Proton finally was able to post a profit of RM140 million in 2008 after declaring a loss of about RM600 million in 2006. This paper will unveil and relate the leadership style theory that has enabled the company to turnaround into the black in two short years.It will also identify the gaps that should be implemented in the Business Turnaround Plan. The gaps identified could possibly accelerate the turnaround process and become a lead to future study in reference to the leadership transformation topic.